A Simulation Study On Performance Of Photovoltaic Thermal Water (PVTW) Collector Under Different Loading Of Mass Flow Rate Using ANSYS Fluent - Akop, Mohd Zaid; Lai, Tian Wei; Salim, Mohd Azli; Mohd Rosli, Mohd Afzanizam; Abdul Hamid, Nurfaizey; Mansor, Muhd Ridzuan; Md. Saad, Adzni; Mohamed Arifin, Yusmady; Herawan, Safarudin Gazali (Penerbit UniMAP, 2021)
The renewable energy has been a widely grown field fascinated by the researchers and scientist from the public and private sector. Solar energy is considered as the most abundant energy in the present world. The purpose of this research is to determine the performance of photovoltaic thermal water collector under different design of absorber tube in steady state condition. The computational fluid dynamics (CFD) simulation is carried out by using ANSYS Fluent software. This study used the geometry drawn in computer-aided design (CAD) software SolidWorks. The model drawn are spiral, horizontal serpentine and vertical serpentine absorber tube. The model drawn in SolidWorks software is then imported into ANSYS Fluent model to obtain the meshed model. The photovoltaic panel used in this project is silicon-based photovoltaic cell. The performance of photovoltaic thermal water collector is determined with the summation of electrical performance from the photovoltaic panel and thermal performance from the solar collector under 0.001 kg/s to 0.005 kg/s with intervals 0.001 kg/s. The relationship between water mass flow rate and solar irradiance intensity on performance photovoltaic thermal system was determined. At 1000 W/m2, spiral absorber photovoltaic thermal water collector has the highest overall performance of 34.96% followed by vertical serpentine absorber of 34.07% while horizontal serpentine absorber has the lowest overall performance of 33.59%. Recommendations are proposed to improve the overall performance of the photovoltaic thermal water collector system.